Immunogenicity of recombinant HS ABA392 protein vaccine against haemorrhagic septicaemia in animal model / Rita Devi Velappan @ Morthy - Rita Devi , Velappan @ Morthy (2018)
Haemorrhagic septicaemia (HS) outbreak has a major impact in Asian countries, where farmers encounter economic lost due to death and low milk production. HS occurred most commonly in cattle and buffaloes. The first HS outbreak reported in Malaysia was in the year 1900 which caused huge lost to the meat and dairy industry. Pasteurella multocida has a pathogenic potential in vertebrate animals. P. multocida serotype B: 2 is the etiology for HS in Asia thus contribute highest mortality rate of cattle and buffaloes. There are four types of vaccine used in all the countries namely, alum precipitated vaccine, broth bacterins, aluminum hydroxide gel vaccine and oil adjuvant vaccine (OAV). The function of DNA recombinant technology such as gene cloning and expression to produce recombinant proteins from P. multocida, could trigger immune response and provide protective immunity to the administered animal. The recombinant clone ABA392 which used in this study was derived from P. multocida serotype B strain 202 (PMB202). ABA392 gene was successfully cloned into pET-30a an expression vector and known as ABA392/pET30a. The size of expressed protein was determined as ~32 kDa and confirmed via immunoblotting. The protein was further purified using Immobilized Affinity Chromatography (IMAC) technique. The purified protein was tested on rats for the immunogenicity along with positive and negative control groups. Blood was collected weekly for 7 weeks consistently. Enzyme-Linked Immunosorbent Assay (ELISA), Total White Blood Count (TWBC), Renal Function Test (RFT) and Liver Function Test (LFT) were performed. Lung, heart, liver and kidney organs were collected and processed for histopathology analysis. No significant changes were observed in the entire organs from each group. The purified protein from recombinant clone ABA392/pET-30a has induced high titer antibody compared to positive and negative group. Total white blood count shows leukocytosis. The RFT and LFT were in normal values in the vaccinated group. Recombinant clone ABA392/pET-30a has been expressed purified and has been tested on laboratory rat. Since the expressed protein has the capability to provoke immune response, challenge studies using P. multocida serotype B: 2 against this protein are required to enhance the efficient of this protein as a vaccine against HS in future.